Climate Change in Mountain Regions: Adaptation Strategies And Future Sustainable Development Alternatives. Valmalenco Case Study - Dematteis, Margherita (2022)
In the current context of climate change, mountain areas and tourist destinations in the Alps face common challenges. The impacts of climate change, resulting in a reduction in natural snow cover, changing tourist practices and demographic dynamics require strategies for the diversification of tourism supply and regional development. In response to these challenges, through a participatory and inclusive approach of local communities, the study aims at investigating and implementing new models of sustainable tourism, economic, social and environmental development. Through the analysis of the ski area of Chiesa in Valmalenco, we analyze the critical challenges facing the snow industry and aim at the development of forms of tourism alternative to the ski sector, with the aim of strengthening the mountain economy, the resilience of local communities and investigating possible strategies to adapt to climate change. Unfortunately, even today the winter ski industry is too large a lobby, it requires intensive use of resources and attracts an unsustainable type of tourism with a high environmental impact. Through the analysis of a number of case studies in various locations in the Alps, linked to positive experiences of alternative tourism development, concrete examples of active and innovative projects in the area are investigated. The expected final objectives include analyzing the vulnerability of the traditional tourism system, linked to the ski industry, promoting sustainable economic transition processes, assessing the replicability of these experiences in other Alpine contexts, and fostering concrete experiences of resilience and adaptation.